Need help from an expert?
The world’s top online tutoring provider trusted by students, parents, and schools globally.
To integrate (x^2+1)/(x^3+1), use partial fractions and substitution.
First, factorise the denominator using the sum of cubes formula:
x^3+1 = (x+1)(x^2-x+1)
Then, use partial fractions to write the integrand as:
(x^2+1)/(x^3+1) = A/(x+1) + Bx+C/(x^2-x+1)
To find A, multiply both sides by (x+1) and substitute x=-1:
A = (-1^2+1)/((-1+1)(-1^2-1+1)) = 1/3
To find B and C, multiply both sides by (x^2-x+1) and substitute x=0 and x=1:
B+C = 0
B+C = 2/3
Solving these equations gives B=1/3 and C=-1/3.
Substitute these values back into the partial fractions expression:
(x^2+1)/(x^3+1) = 1/(3(x+1)) + (x+1)/(3(x^2-x+1)) - 1/(3(x^2-x+1))
Now, use the substitution u=x^2-x+1 and du=(2x-1)dx:
∫(x^2+1)/(x^3+1) dx = (1/3)ln|x+1| + (1/6)ln|x^2-x+1| - (1/3)∫du/u
The final integral can be evaluated using the natural logarithm:
∫du/u = ln|u| + C = ln|x^2-x+1| + C
Therefore, the final answer is:
∫(x^2+1)/(x^3+1) dx = (1/3)ln|x+1| + (1/6)ln|x^2-x+1| - (1/3)ln|x^2-x+1| + C
= (1/3)ln|x+1| - (1/6)ln|x^2-x+1| + C
Study and Practice for Free
Trusted by 100,000+ Students Worldwide
Achieve Top Grades in your Exams with our Free Resources.
Practice Questions, Study Notes, and Past Exam Papers for all Subjects!
The world’s top online tutoring provider trusted by students, parents, and schools globally.